Microstructure, mechanical and corrosion properties of Co- and Cu-free AlxCrFeNi2.5Mo1-x high entropy alloys. (February 2023) - Liu, Jia; An, Xuguang; Zhang, Jing; Kong, Qingquan; Li, Qiangguo; Wang, Hui; Yao, Weitang; Wang, Qingyuan
Abstract: A series of Alx CrFeNi2.5 Mo1-x high-entropy alloys (HEAs) were prepared by vacuum arc melting. The effects of Al/Mo content on phase, microstructure, mechanical and corrosion properties of as-cast Alx CrFeNi2.5 Mo1-x alloys were investigated. With the increase of Al content, the phases of Alx CrFeNi2.5 Mo1-x alloys evolve from FCC + σ phase (x = 0, 0.2) to FCC + BCC + σ phase (x = 0.5, 0.8) and finally to FCC + BCC phase (x = 1.0) and the microstructure evolves from typical hypoeutectic composed of the eutectic lamellar and interdendrite structure to hypereutectic composed of dendritic and lamellar eutectic structure. Among all the alloys, the Al1.0 CrFeNi2.5 alloy exhibits excellent comprehensive mechanical properties with the yield strength, ultimate tensile strength, elongation and hardness of 502 MPa, 1090 MPa, 16.8% and 336 HV, respectively. Moreover, Mo element is beneficial to improving the pitting corrosion resistance of Alx CrFeNi2.5 Mo1-x alloys in 3.5 wt.% NaCl solution but it could promote the formation of σ phase, which leads to an uneven distribution of Cr elements and reduce the resistance to localized corrosion. Highlights: The Alx CrFeNi2.5 Mo1-x (x = 0, 0.2, 0.5, 0.8, 1.0) alloys were prepared by arc-melting and subsequent copper mold suction casting. With the increase of Al/Mo molar ratio, the crystal structure transforms from FCC + σ phase to FCC + σ + BCC phase, and then to FCC + BCC phase. Al1.0 CrFeNi2.5 alloy with dual-phase phase exhibited better mechanical properties. The Al0.5 CrFeNiMo0.5 alloy possesses excellent comprehensive corrosion resistance in 3.5 wt% NaCl.